Hubungan antara Kualitas Tidur dan Pertumbuhan dan Perkembangan pada Anak Usia Balita - Salma Qothrunnada; Fitriyani Fitriyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
Sleep is an essential need in children's health, but sleep disorders can negatively impact children's health and growth and development. This study aims to assess the relationship between sleep quality and the growth and development of toddler-age children in the Karangdadap Pekalongan, Central Java. A correlative descriptive study with a cross-sectional approach was conducted on 267 children aged 1-3 years. Data collection from October to December 2023 used scales, microtoise, KMS GRAPHS, DDST II, and BISQ questionnaires. Data were analyzed using descriptive statistics and the Chi-Square test. The majority of respondents (82.4%) had good sleep quality. The study showed that there was a significant relationship between sleep quality and child growth; children with sleep disorders had a higher risk of undernutrition and overnutrition (p = 0.0001; OR = 5.260). Sleep quality was significantly associated with child development; children with sleep disorders were at a higher risk of suspected developmental issues (p = 0.0001; OR = 37.217). Sleep quality is highly related to the growth and development of preschool children. Sleep disorders have the potential to reduce the quality of child growth and development, making it important to manage and address sleep disorders to support children's health.